Placenta crucially affects formation of fetal congenital heart disease - V. I. Tsibizova; T. M. Pervunina; V. A. Artemenko; V. O. Bitsadze; K. E. Gotsiridze; I. I. Averkin; D. V. Blinov; N. Yu. Novikova (IRBIS LLC, 2022)
It has been increasingly recognized that structural abnormalities and functional changes in the placenta can adversely affect developing fetal heart. In this article, we examine a role of the placenta as well as potential impact of placental insufficiency on a fetus with congenital heart disease (CHD). The fetal heart and placenta are directly connected because they develop simultaneously with common regulatory and signaling pathways. Moreover, placenta-associated complications are more common in pregnant women carrying fetus with CHD, and the fetal response to placental insufficiency may lead to postnatal preservation of remodeled heart. The mechanisms underlying this placenta-fetus axis potentially consists of genetic factors, oxidative stress, chronic hypoxia, and/or angiogenic imbalance. Thus, the mother-placenta-fetus circulation is critical in understanding the CHD formation. It is necessary to study the changing factors involved in these processes for early identification, imaging, quantification of placental insufficiency, and development of new prenatal therapies in the CHD patient population.